Dermatology Clinical Case Modules: 70-Year-Old Man With a Red Crusty Bump on His Right Arm - Lisa Nguyen; Meera Mahalingam; Amit Garg (Association of American Medical Colleges, 2010)
Abstract This clinical case module is part of a series of online modules being developed for the medical student curriculum in dermatology. This self-directed resource serves as a supplement to traditional lecture and clinical teaching. The purpose of this module is to help students develop a clinical approach to the evaluation and initial management of patients presenting with suspicious growths, particularly actinic keratoses and squamous cell carcinoma. In this case, a 70-year-old man presents with an arm growth and facial lesions. As students navigate through the module, they are presented with various decision branch points in the care of the patient. Based on these decisions, students may follow a variety of sequences. In this way, the module more closely mimics a true clinical experience as students are able to see the consequences of their clinical decision-making. A brief summary of key points on the clinical topic (including epidemiology, etiology, treatment, and prognosis) can be reviewed at the end of the module. The module requires PowerPoint 2007 or Microsoft Office 2007 compatibility. Computer-assisted instruction has been shown to be at least as effective as traditional lecture in teaching dermatology morphology to medical students. The effectiveness and significance of the present work have yet to be determined. We plan to use online pre- and postassessments to evaluate the effectiveness of this module.